2022
DOI: 10.1111/cob.12526
|View full text |Cite
|
Sign up to set email alerts
|

Obesity increases the risk for upper extremity deep vein thrombosis and pulmonary embolism in patients with upper extremity central venous catheters

Abstract: The morbidity and mortality of deep vein thrombosis (DVT) remain a significant burden for the healthcare system. The aim of this analysis was to examine the association of upper extremity central venous catheter (UECVC) and venous thromboembolism (UEVTE) with increasing body mass index (BMI) in a large database study and to further examine disposition. Inpatient data from the National Inpatient Sample from 2017 to 2019 were used to investigate the effect of obesity on patients diagnosed with DVT of the upper e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…We also found an association between obesity and longer catheter dwell time. Interestingly, this factor has been described in the literature as a risk factor for catheter colonization and CRI [ 31 , 32 ], as well as for DVT [ 33 , 34 ]. Strategies to prevent catheter-related intravascular complications could thus be particularly beneficial in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…We also found an association between obesity and longer catheter dwell time. Interestingly, this factor has been described in the literature as a risk factor for catheter colonization and CRI [ 31 , 32 ], as well as for DVT [ 33 , 34 ]. Strategies to prevent catheter-related intravascular complications could thus be particularly beneficial in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…11-13 Recent literature suggests that the incidence of UE DVT may be higher in patients who are overweight, have cancer, or have recently had a peripherally inserted central catheter (PICC line) inserted to deliver life-saving medications to a patient. 14-16 Interestingly, UE DVT is also possible in younger throwing athletes due to interstitial trauma from the repetitive forces of throwing during baseball that resulted in an effort thrombosis. 17…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Recent literature suggests that the incidence of UE DVT may be higher in patients who are overweight, have cancer, or have recently had a peripherally inserted central catheter (PICC line) inserted to deliver life-saving medications to a patient. [14][15][16] Interestingly, UE DVT is also possible in younger throwing athletes due to interstitial trauma from the repetitive forces of throwing during baseball that resulted in an effort thrombosis. 17 An original study from Riddle et al 18 found that care of outpatients who were at risk for PDVT could potentially be improved by use of the clinical decision rules developed by Wells et al, 19 although more study was warranted.…”
Section: Introductionmentioning
confidence: 99%